The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12659/msm.905126
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-588 is downregulated and may have prognostic and functional roles in human breast cancer

Abstract: BackgroundWe explored the expression pattern, prognostic potential, and functional role of microRNA-588 (miR-588) in human breast cancer (BC).Material/MethodsThe expression pattern of miR-588 was assessed by qPCR in BC cell lines and human BC carcinomas. The correlations between miR-588 and BC patients’ clinicopathological characteristics, as well as BC patients’ overall survival, were statistically assessed. In in vitro culture, MCF-7 and MDA-MB-231 cells were infected with lentivirus to overexpress endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…In the present study, the downregulation of miR-588 in OS was demonstrated to be associated with MSTS staging of patients with OS, which was consistent with the previously reported miRNA expression profile of OS (22). Similar findings in breast cancer showed that significant miR-588 downregulation could promote cancer cell proliferation and decrease cisplatin chemosensitivity (18). Furthermore, miR-588 downregulation also predicted the poor prognosis of patients with OS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the downregulation of miR-588 in OS was demonstrated to be associated with MSTS staging of patients with OS, which was consistent with the previously reported miRNA expression profile of OS (22). Similar findings in breast cancer showed that significant miR-588 downregulation could promote cancer cell proliferation and decrease cisplatin chemosensitivity (18). Furthermore, miR-588 downregulation also predicted the poor prognosis of patients with OS.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, miR-588 expression and MSTS staging were demonstrated to act as independent prognostic factors for OS. The prognostic value of miR-588 was also previously demonstrated in breast and prostate cancers (18,19). The prognostic value of miRNAs has drawn special attention in previous studies, and several miRNAs have been identified as independent prognostic indicators for various types of cancer (30).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…More specifically, our data suggest that low expression of miR-588 is a poor prognostic factor in GC patients. Consistent with our findings, miR-588 has been reported to be expressed at low levels in lung squamous cell carcinoma and breast cancer, and this low expression was associated with unfavorable patient prognosis [ 11 , 17 ]. In contrast, in human prostate cancer and ovarian cancer, miR-588 was shown to be overexpressed in tumor cells and tissues [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…MiR-154 reduces the LSCC growth by inhibiting GALNT7 [ 19 ]. Meanwhile, it has been demonstrated that miR-588 serves as a tumor inhibitor in various cancers, such as lung and breast cancer [ 20 , 21 ]. Moreover, chemokine receptor 4 (CXCR4) is abnormally expressed in LSCC and contributes to LSCC malignant progression [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%